2018
DOI: 10.4103/ejd.ejd_31_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of professional and laypeople evaluation of nasolabial esthetics following unilateral cleft lip repair

Abstract: Objectives:The objective is to know the extent of agreement of clinicians’ perception of nasolabial esthetic compared to that of laypeople (parents).Materials and Methods:This was a prospective study of comparison of clinician's perception of nasolabial esthetics with that of laypeople following surgical repair of UCL. Participants were recruited from the Cleft Clinic of the Lagos University Teaching Hospital, and surgical repair of the cleft was performed under general anesthesia. Surgical evaluation was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…More recently, Mulder et al (2018) concluded that there were no differences between professionals and laypeople in the assessment of nasolabial appearance on cropped photographs using the CARS. Adetayo et al (2018) found that there were no significant differences when professionals and laypeople graded the lip, but for grading the nose laypeople reported significantly poorer scores, using direct panel assessment. Alhayek et al (2019) reported that professionals rated facial appearance of patients with repaired clefts significantly lower than laypeople using a visual analogue scale, but professionals had a higher perceived need for further treatment.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, Mulder et al (2018) concluded that there were no differences between professionals and laypeople in the assessment of nasolabial appearance on cropped photographs using the CARS. Adetayo et al (2018) found that there were no significant differences when professionals and laypeople graded the lip, but for grading the nose laypeople reported significantly poorer scores, using direct panel assessment. Alhayek et al (2019) reported that professionals rated facial appearance of patients with repaired clefts significantly lower than laypeople using a visual analogue scale, but professionals had a higher perceived need for further treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Currently, there are no objective measures to guide revision decisions, and decisions are made based on preferences of the patient, guardian, and surgeon. Prior research has shown both parents and cleft surgeons often have a critical eye and increased awareness of SCLD (Eliason et al, 1991;Papamanou et al, 2012;Chung et al, 2013;Adetayo et al, 2018). Although the adults' concern for negative perception of the SCLD by peers often drives the decision for revision prior to the child starting school, it has not previously been investigated if peers, who are young children and adolescents, objectively notice SCLD to the same degree as adults.…”
Section: Discussionmentioning
confidence: 99%
“…12 To date, the most common application for eye-tracking in plastic surgery has been to assess observer gaze in subjects with cleft lip and SCLD. 1,3,13,14 However, these studies do not consider how cleft lip pathology affects facial viewing patterns in different groups of individuals.…”
Section: Introductionmentioning
confidence: 99%